Desain Sistem Penunjang Keputusan untuk Produksi Buah-Buahan Unggulan Nasional - Santosa Santosa; Bambang Pramudya; Moeljarno Djojomartono; Sutrisno Sutrisno; Kudang B Seminar; Slamet Susanto (agriTECH, 2006)
The objectives of the study are : (1) to design  land  suitability database for cultivation of the national valuable fruits, (2) to design the activation information of  fruits production, including land preparation until primary postharvest handling, and (3) to design the decision support system for valuable fruits on people’s orchads to produce fresh fruits. The study was conducted in Yogyakarta Special Region, from November 1999 until March 2000.  Two kinds of data used in this study were: (a) primary data, from the direct discussion with the experts, and direct observation in the fruits production center, and (b) secondary data were collected from library studies and Agriculture Agency Offices in each regency or municipality of the Yogyakarta Special Region.  The data in the salaccias production center was established from farmers which owned orchad more than one hectare. The results of  the study were : (1) land suitability database for national valuable fruits cultivation based on relational data, (2) computerize information system, namely Salaccia (Pondoh cultivar) and Mango (Arumanis, Manalagi, Golek, and Gedong cultivar) included : land preparation, planting, fertilizing, cultivating, pest and disease control, pruning, irrigating, harvesting, cleaning of fruits, sorting of fruits, grading of fruits, ripening (specially for mango), and storage of fruits, and (3) the system has been done to determine land suitability for fruits in Yogyakarta Special Region, and the result showed that 62.39 % was suitable between output system designed and the fruits produced by the farmer, namely manggistas, pineapples, mangoes, rambutans, durians, salaccias, and lawzons.